Financial Management Information System within Government Institution and Supply Chain Strategy: Implementation Technology Acceptance Model (TAM) - Citrawati Jatiningrum; Rita Irviani; Fauzi Fauzi; Abdul Halim; Supriyadi Supriyadi (International Journal of Supply Chain Management, 2019)
The provision of comprehensive financial information by the government institution is needed by the wider community to boost the effectiveness of the information to the society and government, and decision-making. This system produces information that is able to encourage the realization of a clean, transparent, and able government to respond to changing demands effectively. Therefore, the success of the information system if the users are successful in the model of acceptance of the systems and information technology and it would be improving their performance. This research aims to examine the acceptance of regional financial information systems in government using the Technology Acceptance Model (TAM) and evidence of its influence on the performance. The study found 556 respondents who are civil servants in Lampung Province. The finding using SEM analysis shows that all constructs have an effect in conformity with the concept of TAM in a government institution. This study reveals that all variables which include the model of TAM theory have a positive impact on the user's performance. It also improves the effectiveness of the information system within the government institution, especially the implementation of the financial management information system.